Perancangan Pengembangan Interior Stasiun Kai Antarkota Kiaracondong Bandung Dengan Pendekatan Ergonomi - Sekar Murti, Martha; Friestya, Doddy; Salayanti, Santi (eProceedings of Art & Design, 2024)
Kiaracondong Station, one of the largest stations in Bandung City, faces a significant increase in passenger volume, resulting in ergonomic issues related to space layout and circulation. This study evaluates the impact of increasing user numbers on comfort and circulation efficiency at the station, and designs solutions based on ergonomic principles. The research methods include direct observation, interviews, and analysis of space usage data. Findings indicate that poorly organized circulation pathways hinder passenger mobility and create potential injury risks. Proposed solutions include separating zones based on user mobility speeds, reorganizing waiting areas, and adding facilities that support passenger needs, such as trolley areas and comfortable seating. The design approach prioritizes ergonomics and open linear circulation to enhance efficiency, safety, and comfort at Kiaracondong Station. Keywords : design; interior; station; Kiaracondong; ergonomics; Bandung City